Control of compliant legged quadruped robots in the workspace. (February 2015) - Gor, M M; Pathak, P M; Samantaray, A K; Yang, J-M; Kwak, S W
Locomotion control of a quadruped robot requires a well-defined gait pattern (i.e., a coordinated actuation of its four legs in some particular fashion with respect to time). It is of practical importance to move the leg tips in a desired trajectory in order to achieve specific objectives such as to avoid obstacles, minimize energy consumption and locomotion time. Along with body displacement, body orientation is an equally important limit parameter during each leg step of the gait pattern. There are several possible gait patterns that maintain stable and aesthetically pleasing locomotion, and most of these are biologically inspired. This article presents quadruped locomotion control in the workspace through a novel control scheme in which the leg forward motion is controlled in the workspace while the body forward motion is controlled by providing the required effort directly to the joint actuators. In this control approach, the leg tip trajectory error drives a proportional-integral controller that is then transformed through the Jacobian to generate the corrective joint torques. For the body forward motion, leg motion is arrested and the joints are provided with opposite motion, which are controlled by a proportional-integral-derivative controller. The proposed method is simple and easy to implement in the workspace. The performance of the proposed control scheme is evaluated through simulations and animations.